PENGARUH PARTISIPASI MASYARAKAT TERHADAP TRANSPARANSI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDesa) - Gunawan, Andi (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
This research was conducted to know the significant level of Effect of Public Participation on Transparency of Rural and Village Expenditure Budget Management (APBDesa) partially showed that Community Participation has a positive and significant impact on Transparency of Village Revenue and Expenditure Budget Management (APBDesa) with the result of the 6,205> 1,983 tables and Has a sig value (probability) of 0.000 which is smaller than 0.05, it indicates that community participation is stronger in influencing the variables of Transparency Management of Revenue and Expenditure Budget of Village (APBDesa). From the results of the research, it was found that the influence of public participation on the transparency of the management of the village income and expenditure budget (APBDesa) in Telagamurni village in the Cibitung sub-district showed that community participation had a positive effect on the transparency of village revenue and expenditure budget management (APBDesa)